Making Scientific Inquiry Activities Accessible to Students with Autism - Ackerman, Alonna (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
In light of the major trend within science education of focusing on inquiry-based activities, students with autism may face difficulties in the classroom due to barriers such as problems with communication, social situations, and desire for routine (Hedges et al., 2014). Though research regarding inquiry-based science education for students with autism is scarce, explicit instruction appears to be a promising option for elementary students (Knight et al., 2012). Additionally, Applied Behavior Analysis and Self-Regulated Strategy Development have proven useful in other content areas (Casey et al., 2014; Ryan et al., 2011; Szapacs, 2006). Extrapolating from this data, the author discusses how these strategies could be applied in inquiry-focused science classrooms and suggests that researchers use these strategies as starting points for future research.